Manipulasi Kekuasaan dalam Pilkada Serang 2024: Analisis Yuridis terhadap Pelanggaran Pemilu yang Terorganisir - Rahayu, Cantika Tresna; Revalina S. V, Ni Komang; Karaniya, Avishtya Siti; Nisa, Rifa Fadhilahtun (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The 2024 Serang Regional Election (Pilkada) drew significant attention due to allegations of electoral violations committed in a structured, systematic, and massive (TSM) manner, which led to a dispute in the Constitutional Court over the Election Results Dispute (PHPU). The purpose of this study is to examine how such TSM violations impact the principles of direct, general, free, confidential, honest, and fair elections (luber-jurdil), as well as how these violations affect the legitimacy of the election results. A normative and empirical juridical method is used in this research to explore the classification of violations, the effectiveness of relevant institutions in enforcing electoral law, and the challenges in proving and addressing organized violations within the existing legal framework.